The Influence of Personnel Abilities and Facilities Faslabuh Mentigi's Dermaga on Readiness Operating KRI in The Lantamal IV Area - Hermawan, Sonny; Khabibi, Nur (Jurnal Perikanan dan Kelautan, 2022)
The purpose of this study was to analyze the influence of the capabilities and infrastructure of the personnel at the Mentigi pier Faslabuh on the readiness of KRI operations in the Lantamal IV area. This study uses a quantitative-associative method with a population of 99 personnel and the determination of the sample using the Slovin formula above, the sample size is 49.75 (rounded to 50 personnel). Data collection using questionnaires and data analysis techniques using multiple linear regression analysis using SPSS. The results showed that there was a significant influence as well as a unidirectional relationship which meant that the increase in the ability of personnel and infrastructure at the Mentigi pier facility would also increase the operational readiness of KRI in the Lantamal IV area